2020
DOI: 10.1016/j.jid.2020.03.933
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Mineralocorticoid Receptor Inactivation Affects the Homeostasis of All Skin Layers in Chronologically Aged Mice

Abstract: The increased production of endogenous glucocorticoids (GCs) in the skin of the elderly population contributes to age-related defects strikingly similar to those occurring after pharmacologic treatments with GCs. GCs act through the ligand-dependent transcription factors GC receptor (GR) and mineralocorticoid receptor (MR). We reported that epidermal MR plays nonredundant roles relative to GR in adult mouse skin homeostasis; however, its relative contribution to natural skin aging has not been previously inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…Also, keratinocyte‐specific alterations in MR EKO may shift the homeostasis of other skin compartments, leading to differential glucocorticoid responses in the whole tissue (Figure 3). These data are in line with the fact that epidermal MR loss has paracrine actions on dermal adipocytes in middle‐aged MR EKO mice (Bigas et al, 2020).…”
Section: Therapeutic Use Of Mr Antagonists In Skin Diseasessupporting
confidence: 81%
See 2 more Smart Citations
“…Also, keratinocyte‐specific alterations in MR EKO may shift the homeostasis of other skin compartments, leading to differential glucocorticoid responses in the whole tissue (Figure 3). These data are in line with the fact that epidermal MR loss has paracrine actions on dermal adipocytes in middle‐aged MR EKO mice (Bigas et al, 2020).…”
Section: Therapeutic Use Of Mr Antagonists In Skin Diseasessupporting
confidence: 81%
“…In this model, MR up‐regulation correlated with ageing‐related adverse changes in the skin, which were suppressed by topical application of spironolactone (Nagase et al, 2013). Recent work also demonstrated that epidermal MR is involved in physiological skin ageing due to enhanced levels of endogenous skin glucocorticoids (Bigas et al, 2020). Although middle‐aged control mice featured partial atrophy in all skin compartments, histopathological and molecular changes in MR EKO mice were compartment specific (Figure 3).…”
Section: Mouse Models To Assess Mr Function In the Skinmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, an increase in MR expression in keratinocytes induces atrophy of the mouse epidermis (Sainte Marie et al, 2007 ), whereas mice in which the MR was inactivated in epithelial cells showed increased keratinocyte proliferation and differentiation (Boix et al, 2016 ). Deletion of the MR in keratinocytes was shown to alter the homeostasis of all skin layers in aged mice, with reduced dermal thickness and decreased collagen deposition (Bigas et al, 2020 ). We previously showed that topical MR blockade accelerates skin wound healing in diabetic mice (Nguyen et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%